On the sensitivity of Finite Element results in the calculation of the lateral thrust for all-steel buckling-restrained braces. (1st September 2019) - Genna, Francesco
Highlights: The difficulty of computing the lateral thrusts in buckling-restrained braces is discussed. The main cause for this is identified in their sensitivity to imperfections. A comparison is done among several FEM models for the choice of an "optimal" one. An analysis of damage and of asymmetric tension/compression behavior for the BRB core steel is performed. The difficulty in the accurate computation of the lateral thrust in BRB is proved numerically. Abstract: The paper discusses the numerical analysis of all-steel buckling-restrained braces. These devices are designed to work in an inherently unstable regime, and their behavior is acutely sensitive both to any configuration detail in reality, and to any adopted parameter in their analysis. Their dissipative axial behavior can be reasonably well predicted by any suitable FEM model, if a good constitutive law is available. Nevertheless, it is shown here that an apparently accurate FEM calculation of the lateral contact forces, generated by the buckled core when it contacts the external containment profiles, produces results so sensitive to modelling details that they are practically devoid of an acceptable degree of accuracy. These observations might raise some doubts about the advisability of employing this type of bracing in normal engineering practice. In our viewpoint, a similar conclusion could be reached for any structural element designed to work in an unstable regime, unless the imperfections – of any type, including possible modelling details – could be explicitly taken into account, either parametrically or in a statistical way.